Collaboration between State and Church in Teacher Education Programme for Development in Kenya in the Last Fifty (50) Years of Independence - A. Kafu , Patrick; Nasimiyu, Genevieve (African Journal of Education,Science and Technology (AJEST), 2015)
Collaboration in education, and especially Teacher education programme, is an emerging trend In Kenya, this feature emerged after the First World War (1914 – 17). It was then and still is viewed as one of the strongest pillars of promoting quality in education. This is because collaboration is usually purposeful, focused academic endeavor geared towards established goals, objectives and shared interest. Generally, this practice in education refers to partnership, association or mutual willingness to work together between individuals, organizations/institutions and nations with common interests. The purpose of collaboration is usually to create opportunity for the involved parties to share unique experiences, resources, expertise and logistics in matters related to education and especially Teacher Education programme. It is intended to enrich the curricula, add value to the practiced education system and promote the quality of education in general and Teacher education programme in particular. In Kenya, collaboration in Teacher education programme between the state and church is not a new development. It can be traced from the colonial era. Its genesis is founded in the Phelps-Stoke and the Beecher education commissions. This paper examines the concept of collaboration between the state and church for development in Kenya in the last fifty years of independence, the need for and value of this process in administration of Teacher education programme in Kenya, the challenges of this trend in the Teacher education programme, lessons Kenya has drawn from practicing thisapproach in the latter programme and the future of collaboration as a tredin education between the state and church in Teacher education programme for development in Kenya.